Pengendali Robot Pebisnis Menggunakan Teknologi Virtual Realty - Andy Satria; Rayhendi Alvio; Joddy Kurniawan (Pusat Riset dan Inovasi Nasional, 2023)
In this study, the creator highlights research regarding one of the advancements in human-made conscious innovation, especially robots. The progress of robots is very complex and currently similar to humans. The examination technique used is to use a written survey by looking at books, diaries and other writings that can be used as reasons for research, with educational provisions it will build scientists' insight and develop information about the problems raised in the research. . In certain countries, robots are widely used and are starting to replace human tasks, for example in Japan, robots are widely used in cafes and accommodation areas. By utilizing robots, human work begins to decrease. This exploration creates opportunities if robots are used in retail or shopping areas, with this system providing suggestions for the advancement of mechanical technology in Indonesia.